1885. Cost-Effectiveness of Ceftazidime–Avibactam Compared With Colistin for Treatment of Carbapenem-Resistant Enterobacteriaceae Bacteremia and Pneumonia. (26th November 2018) - Sfeir, Maroun; Satlin, Michael; Calfee, David P; Simon, Matthew S
Abstract: Background: Ceftazidime/avibactam (CAZ/AVI) may improve outcomes among patients with carbapenem-resistant Enterobacteriaceae (CRE) infections. However, the cost-effectiveness of CAZ/AVI is unknown. Methods: We used a decision analytic model to estimate the health and economic consequences of CAZ/AVI-based therapy compared with colistin-based therapy (COL) for a hypothetical cohort of patients with CRE pneumonia and bacteremia over a 1-year time horizon. Model inputs were from published sources and included CRE mortality with COL (41%), CAZ/AVI's absolute risk reduction (ARR) in CRE mortality (23%), daily cost of CAZ/AVI (1, 080), risk of NTX with COL (42%), probability of discharge to long-term care (LTC) following CRE infection (56%), and improved odds of discharge home with CAZ/AVI compared with COL (1.8). Outcomes included quality adjusted life-years (QALYs), costs, and incremental cost-effectiveness ratios (ICER; /QALY). 1-way and probabilistic sensitivity analyses were performed and ICERs were compared with willingness to pay standards of 100, 000/QALY and 150, 000/QALY. Results: The ICER for CAZ/AVI compared with COL was 110, 300/QALY (table). In 1-way sensitivity analyses, CAZ/AVI had an ICER <100, 000/QALY when the ARR in CRE mortality was >29%, the odds of discharge home with CAZ/AVI was > 1.9, CAZ/AVI's daily cost was <775, quality of life weight following discharge home was >0.92, risk of NTX with COL was >49% or annual costs of LTC were <75, 890. CAZ/AVI had an ICER >150, 000/QALY when CAZ/AVI's ARR in CRE mortality was <12%, the odds of discharge home with CAZ/AVI compared with COL was <1.3, or the quality of life weight following discharge home was <0.61. In probabilistic sensitivity analysis, CAZ/AVI was the optimal strategy in 40% and 76% of simulations at willingness to pay thresholds of 100, 000/QALY and 150, 000/QALY, respectively (figure). Conclusion: CAZ/AVI is appropriate from an economic perspective based on efficacy data from observational studies and willingness to pay standards in the United States. Disclosures: M. Satlin, Allergan: Grant Investigator, Research grant.